Cloning and Gene Expression of AnsZ Encoding L-Asparaginase Enzyme from Local Bacillus sp. - RIMA AZARA; IS HELIANTI; JONI KUSNADI; YUNIANTA YUNIANTA (Microbiology Indonesia, 2014)
L-asparaginase is an enzyme that catalyzes the hydrolysis of L-asparagine into L-aspartic acid and ammonia. In medical aspect, L-asparaginase especially those came from E. coli and Erwinia chrysanthemi used as chemotherapy agent of acute lymphoblastic leukemia (ALL). However, new potential organisms possessing L-asparaginase production capacity with a similar therapeutic effect are still required . In Bacillus subtilis strain 168, there are two kinds of L-asparaginase gene, AnsA and AnsZ. The study of the later L-asparaginase (AnsZ) has not been conducted intensively. The aim of this study is, first, to isolate this gene of L-asparaginase (AnsZ) from local Bacillus sp. and then to express this gene in Escherichia coli. Using PCR-cloning method, an open reading frame (ORF) containing 1128 bp was obtained. The ORF has 99% homology with sequence of L-asparaginase from Bacillus subtilis Bsn5. The gene then was subcloned into pET 21d (+) with his6-tag in the C-terminal of the gene product and expressed in E.coli BL21. L-asparaginase activity analyses showed that recombinant E. coli containing recombinant plasmid with open reading frame (ORF) L-asparaginase (AnsZ) from Bacillus subtilis had higher activity than that is not containing ORF L-asparaginase (AnsZ). Purification with HisPur TM Ni-NTA Purification Kit increased the specific activity of L-asparaginase (AnsZ) enzyme to 29 fold.